Reliable Design and Manufacturing of Thrusters for Marine Vessels - Boopalan J., Sam Prasanna J., Karthikeyan P., Rajendran S., Arul Murugan M., Ganesan G., Sivakumar D., Sakthivel K. (International Journal of Control and Automation, 2020)
Thrusters are essential propulsion systems that provide maneuverability to marine vessels. The reliability of thrusters is critical for safe and efficient vessel operation. This research paper aims to provide an overview of the design and manufacturing process for reliable thrusters. The paper will explore the key design considerations and manufacturing techniques for thrusters, including material selection, component design, testing, and quality control. Additionally, the paper will highlight some of the challenges and future trends in the design and manufacturing of thrusters.